PENGARUH PELAYANAN PUBLIK TERHADAP KEPUASAN MASYARAKAT DI KELURAHAN SUKAMAJU KECAMATAN SAKO KOTA PALEMBANG (STUDI KASUS PELAYANAN SURAT PENGANTAR NIKAH) - Saiton Saiton (Business Perspective Journal, 2021)
ABSTRACT In improving services, employees who are truly of high quality are needed so that interests that follow the basic rights of society can be carried out properly. Every organization, private or public, needs to build human resources that are professionally owned and have high competence. Highly competent employees will be the center of organizational excellence as well as support for organizational competitiveness in entering the era of globalization and facing the business environment and social conditions of society which are experiencing rapid changes. The results of research and discussion, public services at the Sukamaju Urban Village office received a very good assessment (with a score of 81.75). However, of the 12 elements of service quality, there are some elements that are still deemed not fulfilling the wishes of the community. These elements are speed in service and certainty of service schedules. Both elements are in the good category, but the accumulative value is below the value of the other elements. this needs to be improved, so that in the future it can meet community expectations. So that good and satisfying service can really be felt by the community. The community satisfaction felt by the community when dealing with marriage cover letters at the Sukamaju Village office received a very good assessment (with a score of 88.25). Public Service has an effect on Community Satisfaction, the value obtained states that there is a positive influence and between Public Service on satisfaction (79.2%). The results obtained state that if the service is improved, then the community satisfaction will also increase. Keywords: public service, community satisfaction